Techniques & Principles in language teaching - Larsen-Freeman, Diane; Anderson, Marti (Oxford, New York : Oxford Uiversity Press, 2011)
This is an updated third edition of our popular introduction to language teaching methodology, which describes different methods and approaches in language teaching. Clear and jargon-free, it provides practical step-by-step guidance for new teachers, and introduces more experienced teachers to new approaches and teaching ideas. Includes a new chapter on the use of digital technology.
The Grammar-Traslatión Method -- The Direct Method -- The Silent Way -- Desuggestopedia -- Community Language Learning -- Total Physical Response -- Content-based Language Teaching -- Conten Based instruction -- Task-based language teaching...
Resumen tomado de la página web de la editorial
general
Keywords: Inglés -- Gramática; Inglés -- Enseñanza